1996
DOI: 10.1148/radiology.201.3.8939243
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis fistulas and grafts: use of cutting balloons to dilate venous stenoses.

Abstract: To evaluate percutaneous transluminal angioplasty (PTA) with a cutting balloon performed in stenosed hemodialysis fistulas and grafts, 19 venous lesions in 15 patients were treated with a cutting balloon with an inflated diameter of 3-6 mm. The grade of stenosis ranged from 40% to 90% (mean, 65% +/- 15 [standard deviation]). Cutting PTA was performed before conventional PTA in seven patients and was followed with conventional PTA with larger balloons in seven patients. The balloon expanded completely in all pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
1
7

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 0 publications
3
47
1
7
Order By: Relevance
“…Providing successful vascular access for hemodialysis remains one of the most challenging problems [1,2,3,4,5,6,7,8,9,10,11]. Many investigators have reported that Brescia-Cimino arteriovenous fistulas have several advantages to polytetrafluoroethylene grafts, especially for a longer lifetime [1,2,3,4,5,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Providing successful vascular access for hemodialysis remains one of the most challenging problems [1,2,3,4,5,6,7,8,9,10,11]. Many investigators have reported that Brescia-Cimino arteriovenous fistulas have several advantages to polytetrafluoroethylene grafts, especially for a longer lifetime [1,2,3,4,5,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Many investigators have reported that Brescia-Cimino arteriovenous fistulas have several advantages to polytetrafluoroethylene grafts, especially for a longer lifetime [1,2,3,4,5,8,9,10]. Despite the increased reliability, however, Brescia-Cimino arteriovenous fistulas often require radiological or surgical interventions frequently to maintain their function [1,2,3,4,5,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of cutting balloons for treatment of high-pressure balloon-resistant stenotic lesions in AVGs and AVFs has been described in clinical reports and small studies (50)(51)(52)(53)(54). A multicenter randomized clinical trial of 340 patients with venous outflow stenoses reported equivalent 6-month patency rates between PTA alone and cutting balloon angioplasty, but the cutting balloon approach experienced a greater number of device-related complications, including venous rupture and dissections (55).…”
Section: Endovascular Approachesmentioning
confidence: 99%